2011
DOI: 10.1016/j.micinf.2011.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of haemocyte function by exposure to cytochalasin b or nocodazole increases the susceptibility of Galleria mellonella larvae to infection

Abstract: Administration of non-toxic concentrations (10 mM) of cytochalasin b and nocodazole to larvae of Galleria mellonella increased their susceptibility to infection by the yeast Candida albicans. These agents were found to inhibit the process of phagocytosis and to reduce the killing ability of haemocytes. In addition, both cytochalasin b and nocodazole reduced the release of antimicrobial peptides (e.g. apolipophorin 3) and enzymes (e.g. serine protease) from PMA stimulated haemocytes. Rhodamine coupled phalloidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Hemocytes numbers were significantly lower in larvae infected with C. parapsilosis and C. orthopsilosis compared with C. metapsilosis . Correlation of hemocytes numbers with survival after Candida infection has also been observed in other studies 5 , 15 , 31 - 33 and hemocytes function has been clearly linked to the outcome of fungal infections in Galleria 34 , 35 . Gago et al speculated that pseudohyphae production by phagocytosed yeasts may damage hemocytes, thus contributing to the lower number of hemocytes observed.…”
supporting
confidence: 58%
“…Hemocytes numbers were significantly lower in larvae infected with C. parapsilosis and C. orthopsilosis compared with C. metapsilosis . Correlation of hemocytes numbers with survival after Candida infection has also been observed in other studies 5 , 15 , 31 - 33 and hemocytes function has been clearly linked to the outcome of fungal infections in Galleria 34 , 35 . Gago et al speculated that pseudohyphae production by phagocytosed yeasts may damage hemocytes, thus contributing to the lower number of hemocytes observed.…”
supporting
confidence: 58%
“…Although more of the same strains need to be tested in different labs to draw meaningful conclusions, this highlights the potential differences either in wax worms provided by different suppliers, environmental, or experimental conditions. In a recent publication, Banville et al 48 showed that nutritional deprivation led to a reduction in immune response and an increased susceptibility to infection. This does not explain the differences between our study and that conducted by Olsen et al as both our wax worms were starved post-infection.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a particulate fraction of the hemolymph apoLp-III could originate from the hemocytes. Secretion of apoLp-III from isolated G. mellonella hemocytes in vitro has been recently reported [4]. Moreover, release of apoLp-III stored in hemocyte granules into hemolymph upon bacterial infection has been described in H. cunea [24].…”
Section: Discussionmentioning
confidence: 96%